2015
DOI: 10.1371/journal.pone.0127560
|View full text |Cite
|
Sign up to set email alerts
|

Medfly Ceratitis capitata as Potential Vector for Fire Blight Pathogen Erwinia amylovora: Survival and Transmission

Abstract: Monitoring the ability of bacterial plant pathogens to survive in insects is required for elucidating unknown aspects of their epidemiology and for designing appropriate control strategies. Erwinia amylovora is a plant pathogenic bacterium that causes fire blight, a devastating disease in apple and pear commercial orchards. Studies on fire blight spread by insects have mainly focused on pollinating agents, such as honeybees. However, the Mediterranean fruit fly (medfly) Ceratitis capitata (Diptera: Tephritidae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…In addition, starvation and other stresses causing growth arrest, which are experienced during epiphytic stages, in soil, rainwater, vectors, etc., lead to the intracellular accumulation of H 2 O 2 (McDougald et al, 2002). Related to this, the starvationinduced viable but non-culturable (VBNC) response (Oliver, 2010;Ordax et al, 2012Ordax et al, , 2015Santander et al, 2012Santander et al, , 2014a, characterized by the inability of viable cells to grow on routine solid media (Oliver, 2010;Ramamurthy et al, 2014), has been linked to the inability to detoxify H 2 O 2 (Flores-Cruz and Allen, 2011;Imamura et al, 2015;Kong et al, 2004Kong et al, , 2014Zhong et al, 2009). However, the exact contribution of catalases to this process has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, starvation and other stresses causing growth arrest, which are experienced during epiphytic stages, in soil, rainwater, vectors, etc., lead to the intracellular accumulation of H 2 O 2 (McDougald et al, 2002). Related to this, the starvationinduced viable but non-culturable (VBNC) response (Oliver, 2010;Ordax et al, 2012Ordax et al, , 2015Santander et al, 2012Santander et al, , 2014a, characterized by the inability of viable cells to grow on routine solid media (Oliver, 2010;Ramamurthy et al, 2014), has been linked to the inability to detoxify H 2 O 2 (Flores-Cruz and Allen, 2011;Imamura et al, 2015;Kong et al, 2004Kong et al, , 2014Zhong et al, 2009). However, the exact contribution of catalases to this process has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Reports in the literature often use the term excretion to apply to either regurgitation or defecation or both. Studies have shown that microbes can be attached to the legs (Kobayashi et al, 1999), wings (Ordax et al, 2015;Tan et al, 1997;Yap et al, 2008), or other body parts, including the mouthparts (Geden et al, 2008;Sela et al, 2005). The report by Junqueira et al (2017) examined 116 individual blowflies and houseflies on three continents using high-coverage, whole-genome shotgun sequencing and reported that the legs/wings showed the greatest microbial diversity; and, the authors suggested these two fly structures provided an important microbial dispersal route.…”
Section: Mouthpartsmentioning
confidence: 99%
“…Coronado-Gonzalez et al (2008) reported regurgitation of crop contents is mainly the way adult Tephritidae feed while Vijaysegaran et al (1997) showed for adult Bactrocera, not given water and now dehydrated, were unable to ingest dry or semi-solid diets. Ordax et al (2015) demonstrated in the laboratory for adult medfly, C. capitata (i.e. a polyphagous feeder as an adult), when fed Erwinia amylovora Burrill, one of the most important pathogens of apples and pears, was able to harbour the pathogen for up to 8 days inside the digestive tract and 28 days on the wings and other body parts.…”
Section: Regurgitationmentioning
confidence: 99%
“…To address this challenge will require intellectual exercises to forget about pathogenicity to plants and to envisage other, broader environmental roles played by these bacteria, including: (i) those involving interactions with other prokaryotes and with eukaryotes, such as insects; (ii) the mediation of gene expression in plants, animals or other microbes; (iii) as competitors for nutrients or space with organisms in diverse habitats; and (iv) in important Earth system cycles, such as those of water, nitrogen or carbon. There have been efforts to explore the interaction of plant‐pathogenic bacteria with eukaryotes, such as fungi (Wichmann et al ., ) and insects (Hendry et al ., ; Ordax et al ., ; Stavrinides et al ., ). Direct environmental evidence for these associations has not been found to date, but these experimental efforts are based on the presence of genes with putative roles in virulence to insects or fungi in the genomes of these bacteria (Feil et al ., ; Smits et al ., ) and on well‐known and bona fide associations, such as that of Pantoea stewartii with its insect vector (Correa et al ., ).…”
Section: Challengesmentioning
confidence: 99%